Analysis of waste-energy policy in different countries; practices and implication for sustainable development - Kərimov, Elgün; Salmanov, Ceyhun (My University, 2024)
Based on an analysis of world experience, the practice of countries around the world, including Azerbaijan, and having statistical data, we can talk about the prospects for the development of this energy sector. Waste disposal is vital for humanity, primarily from an environmental point of view. There are various waste disposal methods depending on their type. The work describes in detail methods for processing waste and using it as energy and fertilizers. These methods are widely used in countries with developed economies, and in those countries that are not indifferent to the fate of the planet and humanity.
Keywords: Economy of Azerbaijan. Statistic information; Waste to energy policy; The Intergrated solid waste management project; Renewable energy in Azerbaijan’s Liberated Zones